O Educar na Curiosidade no pensamento educacional de Catherine L’Ecuyer - Cintra, Shirley Cristiane (2024)
This dissertation starts from a historical approach to human phenomena and situates the ideas and educational thought of Catherine L’Ecuyer in the globalized, technological, and scientific moment of organization of production and institutions in the final years of the 20th century and the first decades of the 21st century, in order to elucidate how the historical context of the author's intellectual and social formation, associated with his philosophical and pedagogical assumptions, corroborated the formulation of his theory about educate in curiosity. In this scenario, faced with the transformations and contradictions that characterized social life and education during this period, L’Ecuyer advocates the need to rethink educational processes, which, according to her, are affected by the excessive use of digital devices, the belief in hypereducation and overstimulation, in addition to the obsession with the performance and productivity of children and young people of this generation. To this end, she embraces educational concepts and theories from classic authors of philosophy and pedagogy that, in line with its search, would encourage in children a significant encounter with knowledge, curiosity and fruitful educational training. Thus, so that the understanding of his ideas is coherent within the reflection that this dissertation intends to outline, the analysis was carried out through bibliography, in which, as primary sources, were prioritized, the following works by the author: “Educate in curiosity” (2015); “Educate in reality” (2018); and “Maria Montessori in front of the pedagogical legacy of Jean-Jacques Rousseau's romanticism” (2020), as well as her scientific articles published on the topic in question. As secondary sources were chosen for historiography that deals with the historical-social context delimited by the research, which, in this case, will be based on the debates of the following contemporary authors: Bauman, Harvey, Charlot, Desmurget, Wolff, between others. After that, some of the main thinkers of philosophy and classical pedagogy will be investigated, namely: Aristotle, Thomas Aquinas, and Montessori, to understand how their philosophical and educational assumptions relate to the author's theory. Finally, this work aims to unravel how L’Ecuyer’s thoughts – within the proposal of educating in curiosity – can contribute to current reflections on education, not as a formula for the obstacles of this situation, but, supported by the historical time that gave it social reason, it becomes, like so many other educational theories, reference that questions, among other questions, about how substantial it is for educators, teachers, parents and the social body in general to focus on contemporary pedagogical thinking and rethinking, with the aim that we are, in fact, as education researchers, committed to the training of new generations